Sequence Variations of CCAAT/Enhancer Binding Protein α (C/EBPα) gene encoding meat quality in local and exotic cattle breeds - Endang Tri Margawati; Hajar Indra Wardhana; Nani Radiastuti; Slamet Diah Volkandari (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2020)
Gene of C/EBPα is a gene associated with lipid composition and distribution, the gene therefore contributes in enhancing of meat quality. There is no information of sequence variations of C/EBPα gene investigation in local and exotic beef cattle in Indonesia. This research was aimed to detect the presence of sequence variations of C/EBPα gene in local beef and exotic cattle. Twelve samples were used in this study such as Bali cattle (2), Ongole grade (2), Pasundan (2), Friesian Holstein (1), Angus (1), Simmental (2), Limousin (1) and Banteng (1). Several steps of the research were DNA extraction and quantification, amplification (PCR), electrophoresis, sequencing and sequence analysis of C/EBPα gene. DNA was collected either from blood or hair bulbs.  Determination of homolog bases of C/EBPα gene was based on BLAST result while base sequence variation was analyzed by using MEGA 6. The result showed that all cattle samples were confirmed bearing the C/EBPα gene that amplified along of 1,339 bp. and annealing temperature of 54°C. It was obtained three nucleotide variations at the position of 870 (G→A), 931 (A→G) and 1196 (G→A) only found in Bali cattle and Banteng, but there were no nucleotide variations in the local beef cattle, exotic cattle and the sequence reference of Bos taurus (Japanese Black/Acc No. DQ068270.1; Hanwoo/Acc No. D82984.1; Qinchuan/Acc No. NM_176784.2). Those nucleotide variations caused changing of amino acid of Alanine to Threonine at 931 and Asparagine to Serine at 1196. Mutation at position 271 changed nucleotide Cytosine to Adenine (C271A) that found in PO and Simmental cattle. Further research is needed to confirm the changing of amino acid of C/EBPα gene in Bali cattle might affect to meat quality.